Training on Making a Water Speed ​​Detection Tool in Culverts for Early Detection of Flood Disasters in Tanjung Duren Village, DKI Jakarta - Syah Alam; Indra Surjati; Lydia Sari; Iwan Purwanto; Farras Hamidah; Samuel Netazi; Tri swasono adi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
In early 2020, the Greater Jakarta area experienced severe flooding in several areas, one of which was the North Tanjung Duren Village, Grogol Petamburan District, West Jakarta. Based on BMKG data in February 2020, the Tanjung Duren Utara Urban Village area is a flood-prone area with a height of 10-30 cm and is also a densely populated settlement so that it is prone to short circuit hazards that can cause fires. One of the causes of flooding is water channels / culverts that do not flow smoothly. This activity proposes the creation of a water velocity detection device that functions as an early detection of flood disasters. The detection device is designed using a microcontroller and is connected to a sensor for detecting the speed of water flowing from the drain pipe in the culvert. Based on the results of the training provided, the community's improvement in early detection of flood disasters has increased as indicated by an increase in the post-test value of 52% compared to the pre-test value. This activity is very useful for flood-prone areas as an early detection approach.